Local Food Identity and Sustainable Commercial Production: Food Business Entrepreneurs in Chanthaburi Province, Thailand - Yodkham, Ploypailin; Charoenphun, Narin; Yuvanatemiya, Vasin; Singhapreecha, Charuk; Tengsuwan, Parichat; Preepremmote, Patcharee; Phukseng, Thanaphon; Cheawchan, Kanyarat (Asia Social Issues, 2025)
Local food identity highlights the unique qualities of regional cuisine. This research investigates entrepreneurs’ commercial production of locally distinct foods in Chanthaburi Province, Thailand. Using qualitative methods, data was collected through document analysis, surveys, and in-depth interviews with 65 local food establishments. The findings reveal that most entrepreneurs (52.31%) operate small-scale household businesses with at most five employees. Key ingredients include cardamom (8.93%), cowa leaves (6.19%), durian (6.19%), calamondin (5.50%), mangosteen (4.47%), pepper (4.47%), and Etlingera pavieana (3.09%). The commercialization of local food in Chanthaburi primarily focuses on savory dishes (76.92%), with desserts (8.79%), snacks (7.69%), and beverages (6.59%) making up the rest. The most popular savory dish is MooChamuang curry, accounting for 23.88% of menu items. Guidelines for enhancing local food production include improving food standards, promoting healthy diets, supporting the local food movement, advancing gastronomy tourism, and adopting the Bio-Circular-Green (BCG) economic model for sustainability. These findings offer valuable insights for entrepreneurs and stakeholders looking to advance the local food industry and inform strategies for sustainable development.